Provincia, nación y patria: el tratamiento de las identidades en la historiografía vasca - Aizpuru, Mikel; Portillo, José M. (Huarte de San Juan. Geografía e Historia, 2015)
This article analyses the historiographical production of the Instituto Valentín Foronda related to the processes of territorial and national identity formation. First, we consider the contributions from the history of politics and law dealing with the transition from traditional monarchy to liberal State and constitucional monarchy. We secondly pay attention to the historiography about the processes of nation making and its varieties in the Basque Country from late nineteenth century to the present.